Group A Streptococcus M1T1 Intracellular Infection of Primary Tonsil Epithelial Cells Dampens Levels of Secreted IL-8 Through the Action of SpyCEP - Soderholm, Amelia T.; Barnett, Timothy C.; Korn, Othmar; Rivera-Hernandez, Tania; Seymour, Lisa M.; Schulz, Benjamin L.; Nizet, Victor; Wells, Christine A.; Sweet, Matthew J.; Walker, Mark J. (Frontiers in Cellular and Infection Microbiology, 2018)
Streptococcus pyogenes (Group A Streptococcus; GAS) commonly causes pharyngitis in children and adults, with severe invasive disease and immune sequelae being an infrequent consequence. The ability of GAS to invade the host and establish infection likely involves subversion of host immune defenses. However, the signaling pathways and innate immune responses of epithelial cells to GAS are not well understood. In this study, we utilized RNAseq to characterize the inflammatory responses of primary human tonsil epithelial (TEpi) cells to infection with the laboratory-adapted M6 strain JRS4 and the M1T1 clinical isolate 5448. Both strains induced the expression of genes encoding a wide range of inflammatory mediators, including IL-8. Pathway analysis revealed differentially expressed genes between mock and JRS4 or 5448-infected TEpi cells, were enriched in transcription factor networks that regulate IL-8 expression, such as AP-1, ATF-2 and NFAT. While JRS4 infection resulted in high levels of secreted IL-8, 5448 infection did not, suggesting that 5448 may post-transcriptionally dampen IL-8 production. Infection with 5448ΔcepA, an isogenic mutant lacking the IL-8 protease SpyCEP, resulted in IL-8 secretion levels comparable to JRS4 infection. Complementation of 5448ΔcepA and JRS4 with a plasmid encoding 5448-derived SpyCEP significantly reduced IL-8 secretion by TEpi cells. Our results suggest that intracellular infection with the pathogenic GAS M1T1 clone induces a strong pro-inflammatory response in primary tonsil epithelial cells, but modulates this host response by selectively degrading the neutrophil-recruiting chemokine IL-8 to benefit infection.